A master guide to income property brokerage : - Peckham, John M. (Wiley, 2006)
For more than thirty-five years, this guide has been the most reliable, trustworthy resource for real estate brokers and agents who want to increase their commissions and start selling income property. Now in a new Fourth Edition, A Master Guide to Income Property Brokerage is back and better than ever. With significant new material on the Internet and powerful, up-to-date tactics, brokers and agents alike will find in these pages all of the high-quality information they need to succeed. Sixteen power-packed chapters feature step-by-step income-building information that will help you.